An intramolecular, Pd-mediated α-arylation route to 4-aryl-2-naphthols. Issue 33 (12th August 2015) - Aiken, Stuart; Armitage, Ben; Gabbutt, Christopher D.; Heron, B. Mark
Graphical abstract: Abstract: 1-Aryl-1-(2-bromophenyl)but-2-yn-1-ols, obtained from the addition of prop-1-yn-1-yllithium to 2-bromobenzophenones, readily rearrange to 4-aryl-4-(2-bromophenyl)but-3-en-2-ones upon treatment with TFA. Subsequent intramolecular Pd-mediated α-arylation of these but-3-en-2-ones gave 4-aryl-2-naphthols which were smoothly transformed into photochromic naphthopyrans.